ASPEK SPEKTRAL TAPIS INFRAMERAH UNTUK MEMPEROLEH INFORMASI KONDISI TERMAL OBJEK DENGAN KAMERA DIGITAL KONSUMER - , IR. SRI RATNA SULISTIYANTI, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Information about an object can be acquired based on a set of features of the object. Special features objects can also be based on their temperatures. The distribution of temperature variation appears as a texture which is directly related to a specific condition of the object. The implement for this is known as a thermograph. To understand the âmechanismâ of thermography and to benefit from it, a profound study of the sensors used to capture thermal radiation is needed. In addition, the role of filters to stop the visual rays should be investigated as well. This study is intended to explore how far an ordinary consumer digital camera can be used as a thermograph. As a first step, residing infrared stopping filter is removed and three visual light blocking filters are installed in turn. The resulting infrared images are subsequently undergone intensity and contrast normalization and lowpass filtering to fill in the âmissingâ in between gray levels. Finally the richer histogram lines are warped âto matchâ those acquired with the professional thermograph. In terms of entropies, the overall procedures gave an increase from 1.6 to 2.2 with SRS filter, 1.8 to 2.7 with Hoya RM90, and 1.7 to 2.3 with Hoya R72 visible light blocking filters. Color assignments were indeed enhanced the naked eye perception of temperature distributions of the thermal objects of interest.